The impact of perception and presence on emotional reactions: a review of research in virtual reality - Diemer, Julia; Alpers, Georg W.; Peperkorn, Henrik M.; Shiban, Youssef; Mühlberger, Andreas (Frontiers in Psychology, 2015)
Virtual reality (VR) has made its way into mainstream psychological research in the last two decades. This technology, with its unique ability to simulate complex, real situations and contexts, offers researchers unprecedented opportunities to investigate human behavior in well controlled designs in the laboratory. One important application of VR is the investigation of pathological processes in mental disorders, especially anxiety disorders. Research on the processes underlying threat perception, fear, and exposure therapy has shed light on more general aspects of the relation between perception and emotion. Being by its nature virtual, i.e., simulation of reality, VR strongly relies on the adequate selection of specific perceptual cues to activate emotions. Emotional experiences in turn are related to presence, another important concept in VR, which describes the user’s sense of being in a VR environment. This paper summarizes current research into perception of fear cues, emotion, and presence, aiming at the identification of the most relevant aspects of emotional experience in VR and their mutual relations. A special focus lies on a series of recent experiments designed to test the relative contribution of perception and conceptual information on fear in VR. This strand of research capitalizes on the dissociation between perception (bottom–up input) and conceptual information (top-down input) that is possible in VR. Further, we review the factors that have so far been recognized to influence presence, with emotions (e.g., fear) being the most relevant in the context of clinical psychology. Recent research has highlighted the mutual influence of presence and fear in VR, but has also traced the limits of our current understanding of this relationship. In this paper, the crucial role of perception on eliciting emotional reactions is highlighted, and the role of arousal as a basic dimension of emotional experience is discussed. An interoceptive attribution model of presence is suggested as a first step toward an integrative framework for emotion research in VR. Gaps in the current literature and future directions are outlined.